A Combination of Importance and Performance Analysis and Potential Gain in Customer Value for Determining Service Attributes Priority Level for PT. X - Hartono Mulyo Raharjo; Hery Hamdi Azwir (President University, 2018)
As aviation systems across the globe always improving, every aspect in air transport must be in its best condition to support a smooth performance of flight; including ground handling services in airports. Ground handling service is a management system whilst an aircraft is on the ground or during the landing period. The management system is including aircraft maintenance, passenger management, safety and security maintenance, departure control, etc. Soekarno-Hatta International Airport as Indonesia gate to the world is demanded to have best service provided in this airport. PT.X as ground handling service company in the airport receives several complaint from its customers as the company still under development. The company needs to fix this by analyzing the aspects that can affect their customers’ satisfaction. The problem is able to be solved by using Importance and Performance Analysis (IPA) and Potential Gain in Customer Value (PGCV) methods. A combination between these two methods is able to generate an improvement priority ranking that able to use by the company to improve their service performance in accordance with the most potentially give its customer the most satisfaction. There are total of 13 performance of service attributes that is undesirable by the customers. These 13 attributes are in both Main Priority and Low Priority quadrant that is produced by low Performance Level of servicesprovided. Attributes that are located in Main Priority quadrant become the first priority prior to the Low Priority quadrant that will generate lower potential gain for the customers’ satisfaction towards the company.